Truth through proof a formalist foundation for mathematics - Weir, Alan. (Oxford : Oxford University Press, 2010)
'Truth Through Proof' defends an anti-platonist philosophy of mathematics derived from game formalism. Weir develops a more satisfactory successor to game formalism utilising anaccepted broadly neo-Fregean framework, in which the proposition expressed by an utterance is a function of both sense and background circumstance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mathematics -- Philosophy; Logic, Symbolic and mathematical